Synthesis, reactions and antimicrobial activity of benzothiazoles - Abbas, Eman Mostafa; Salem, Marwa Saied; Kassem, Asmaa Fathy; Abd El-Moez, Sherein Ismail; El-Kady, Mohamed Youssef (European Journal of Chemistry, 2015)
Benzothiazoles have been proven to be potent antimicrobial agents. In this study, 3-(5,6-dimethoxy-2-oxo-1,3-benzothiazol-3(2H)-yl)propanohydrazide has been utilized as a scaffold for synthesis of pyrrole, indolylidene, pyrazoles, mercaptotriazole, oxadiazole, triazole and oxothiazolidine derivatives. Structures of the synthesized compounds were elucidated on the basis of elemental analyses and spectral data. All the synthesized compounds were screened for their antimicrobial activity.